Long stem reverse shoulder arthroplasty and cerclage for treatment of complex long segment proximal humeral fractures with diaphyseal extension in patients more than 65 years old. Issue 12 (December 2015) - Garofalo, Raffaele; Flanagin, Brody; Castagna, Alessandro; Lo, Eddie Y.; Krishnan, Sumant G.
Abstract: Introduction: Treatment of long segment proximal humeral fractures with extension below the surgical neck into the diaphysis remains a significant challenge for orthopaedic surgeons. The purpose of this paper was to evaluate the clinical and radiological outcomes following primary long-stem RSA with cerclage fixation for complex long segment proximal humeral fractures with diaphyseal extension in patients more than 65 years old. Material and methods: Between February 2010 and March 2013, 22 patients who suffered a complex proximal humerus fracture with extended diaphyseal involvement underwent surgery with long-stem RSA and cerclages fixation. There were 17 female and 5 male patients, and the mean age was 77.2 years at time of surgery (range 65–84 years). All patients had a 3 or 4-part proximal humerus fracture or a two part fracture with a split of humeral head, with extension to the proximal diaphysis. Clinical and radiographic follow-up was performed on all 22 patients at 6 weeks, at 3, 6, and 12 months postoperatively, and then at 2 years. Clinical evaluation consisted of the shoulder rating Constant scale. X ray evaluation was done to evaluate fracture healing and eventually humeral and glenoid component loosening or other complications. Results: No infections were reported, neither other serious complications. Two patients developed a seroma and one patient developed chronic pain at that was treated with referral to pain management. No patients were lost at follow-up. At final follow-up, average active elevation was 132.5° (range 100°–140°), external rotation 30° (range 55°–10°). Average abduction was 120° (range 90°–135°). The mean adjusted Constant score was 72/100 (range 64–82). All fractures were healed within 3 months after surgery. No loosening of the humeral or glenoid components and no episodes of dislocation/instability were observed in this series. We did not observe scapular notching in any patient on the x-ray at most recent follow-up. Conclusion: Long-stem RSA with cerclages wire fixation represents a viable treatment option for complex long-segment displaced proximal humerus fractures with diaphyseal extension in patients older than 65 years. Our results suggest clinical outcomes at two years of follow up are satisfactory with an acceptable complication rate.